2018
DOI: 10.18311/jbc/2018/17912
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and predatory potential of coccinellids of rice ecosystems

Abstract: ABSTRACT:Coccinellid species belonging to fifteen genera, under five tribes of the family Coccinellidae were collected and identified in this study. Harmonia (Fab.) was the most predominant in southern regions and Coccinella septumpunctata L. was more abundant in the northern and hill regions. Margalef richness index ranged from 9.07 to 14.00 while the species richness directly measured by Hills number H0 ranged from 5-10, with highest species richness present at Malan, Himachal Pradesh. The highest predation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Margalef index measuring the species richness from different zoogeographical habitats of Uttarakhand was 2.1889, 2.7435, 3.3740, 4.5426, and 5.0634 for USN, Nainital, Almora, Uttarkashi, and Chamoli, respectively. Total Margalef's index for Uttarakhand, North India was 5.1911. Shanker et al (2018 evaluate this index to be 10.14 from the rice fields of Almora, which is three times more than our data.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Margalef index measuring the species richness from different zoogeographical habitats of Uttarakhand was 2.1889, 2.7435, 3.3740, 4.5426, and 5.0634 for USN, Nainital, Almora, Uttarkashi, and Chamoli, respectively. Total Margalef's index for Uttarakhand, North India was 5.1911. Shanker et al (2018 evaluate this index to be 10.14 from the rice fields of Almora, which is three times more than our data.…”
Section: Resultscontrasting
confidence: 69%
“…Recently, Rasheed & Buhroo (2018) evaluated biodiversity indices of three districts of Kashmir and found that thirteen ladybird species are evenly distributed in these regions. Similarly, surveys of coccinellid diversity in the rice fields from different states of India revealed high diversity indices from Almora, Uttarakhand (Shanker et al, 2018). This indicates that the coccinellid study of the area has been less studied in the past and there is a need to explore it for future reference.…”
Section: Introductionmentioning
confidence: 99%